1172. Travel-Associated Multidrug-Resistant Organism Acquisition and Risk Factors Among US Military Personnel. (26th November 2018) - Buchek, Gregory; Mende, Katrin; Telu, Kalyani; Kaiser, Susan J; Tribble, David R; Fraser, Jamie; Mitra, Indrani; Lalani, Tahaniyat; Yun, Heather
Abstract: Background: International travel is a risk factor for incident colonization with extended spectrum β-lactamase (ESBL)-producing organisms. These and other multidrug-resistant (MDR) bacteria are major pathogens in combat casualties. We evaluated risk factors for colonization with MDR bacteria in US military personnel traveling internationally for official duty. Methods: TravMil is a prospective observational study enrolling subjects presenting to military travel clinics. We analyzed surveys, antimicrobial use data, and pre- and post-travel self-collected perirectal swabs in military travelers to regions outside the continental United States, Canada, Western or Northern Europe, or New Zealand presenting to one clinic from December 2015 to December 2017. Gram-negative isolates recovered from swabs underwent real-time identification and susceptibility testing (BD Phoenix). Characteristics of trip and traveler were analyzed to determine risk factors for MDR organism colonization. Results: One hundred ten trips were planned by 99 travelers (74% male, median age 38 years [IQR 31, 47.25]); 72 trips were completed by 64 travelers. Median trip duration was 21 days (IQR 12.75, 79.5). Of those with trips completed, 17% traveled to Mexico/Caribbean/Central America, 15% to Asia, 57% to Africa, and 10% to South America; 56% stayed in hotels and 50% in dormitories/barracks. Travelers used doxycycline (15%) for malaria prophylaxis, 11% took an antibiotic for travelers' diarrhea (TD) treatment (fluoroquinolone 7%, azithromycin 4%). Incident MDR organism colonization occurred in eight travelers (incidence density 3.5/1, 000 travel days; cumulative incidence 11% of trips [95% CI: 4%–19%]), all ESBL-producing E. coli . A higher incidence of ESBL-producing E. coli acquisition was associated with travel to Asia (36% vs. 7%, P = 0.02) but not with travel to other regions, TD, or use of antimicrobials. No relationship was seen between fluoroquinolone or doxycycline exposure and resistance to those antimicrobials. Conclusion: Consistent with other studies of US military personnel travelers, incident colonization with MDR organisms following official travel occurs at a lower rate in this population compared with civilian travelers, with no identified modifiable risk factors. The highest incidence of ESBL acquisition was observed during travel to Asia. Disclosures: All authors: No reported disclosures.